Surface-Functionalized Polymeric siRNA Nanoparticles for Tunable Targeting and Intracellular Delivery to Hematologic Cancer Cells - Kwak, Eunji; Kim, Taehyung; Yang, Kyungjik; Kim, Young Min; Han, Hwa Seung; Park, Kyung Hoon; Choi, Ki Young; Roh, Young Hoon (American Chemical Society, 2022)
To date, the application of RNA therapeutics to hematologic malignancies has been challenging owing to the resistance of blood cancer cells against conventional transfection methods. Herein, triple-targeting moiety-functionalized polymeric small interfering RNA (siRNA) nanopartides were systematically developed for efficient targeted delivery of RNA therapeutics to hematologic cancer cells. Polymeric siRNAs were synthesized using rolling circle transcription and were surface-functionalized with three types of targeting moieties-a natural ligand and two additional combinations of cell-specific antibodies-for tunable targetability. As a proof of concept, the optimization of the hyaluronic acid/antibody conjugation ratio was performed for selective intracellular delivery to various non-Hodgkin's lymphoma (NHL) cell lines (Daudi, Raji, Ramos, and Toledo cells) via receptor-mediated endocytosis. The engineered nanopartides showed almost 10-fold enhanced NHL-specific intracellular delivery and induced significant in vitro anticancer effects. This multitargeted nanopartide platform may effectively support the intracellular delivery of polymeric siRNA sequences, and thus promote therapeutic effects in hematopoietic malignancies.